PERANAN LOGISTIK TERHADAP PERUSAHAAN UNTUK MENUNJANG KELANCARAN DUNIA BISNIS - Sutini Sutini; Radian Wismana (Pusat Riset dan Inovasi Nasional, 2021)
There are many activities in the logistics and supply chain management process, starting from the origin of goods (upstream) to the final consumer (downstream), to prepare maritime human resources, especially graduates of the commercial and port shipping management study program, it is necessary to focus on 3 (three) main activities, namely: 1) Procurement; 2) Storage (warehousing); and 3) Delivery. The development of industry and technology that continues to change and is dynamic, as well as the impact of the current covid 19 pandemic where the business logistics and courier service sector is a business sector that has an important role in goods delivery services which is also influenced by people's behavior in online shopping activities or e-commerce. commerce. Vocational higher education, such as diploma three study programs, management of commercial shipping and ports, maritime faculty, Amni Maritime University, Semarang, of course, has the opportunity to prepare human resources and develop their cadets to adapt to the needs of the world of work based on logistical competence and supply chain management so that graduates Commercial and port shipping management study programs can be directly ready to use / plug and play / link and match with the real world of work.